2022
DOI: 10.3390/scipharm90020035
|View full text |Cite
|
Sign up to set email alerts
|

Concepts for New Rapid Simple HPLC Method for Quantification of Fosfomycin Trometamol in Pharmaceutical Dosage Forms with Direct UV Detection

Abstract: Two different concepts for developing direct HPLC-UV methods for quantifying fosfomycin trometamol were developed without any derivatization and modification of the analyte. In the first concept, without the use of alkylamines as ion-pairs in the mobile phase, by using cyanopropyl CN and a strong anion-exchanger column, we investigated the possibility of their highly polar and anion-exchanging forces and mechanisms to retain, separate and detect trometamol without the help of additional agents or modifiers. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
1
1
0
Order By: Relevance
“…The waters C18 (150 × 4.6mm; 5 μm pore size) column at 30 °C performs best among the other columns studied in terms of resolution, symmetry and hence was selected as appropriate for the study. Literature also confirms that, this column was very efficient for resolution of various compounds and its impurities (Piponski et al 2022;Khalil et al 2023). An appropriate mobile phase was finalized by optimizing different composition of mobile phase including ammonium acetate, acetic acid, aqueous ammonia at various strengths.…”
Section: Vaka Et Alsupporting
confidence: 59%
“…The waters C18 (150 × 4.6mm; 5 μm pore size) column at 30 °C performs best among the other columns studied in terms of resolution, symmetry and hence was selected as appropriate for the study. Literature also confirms that, this column was very efficient for resolution of various compounds and its impurities (Piponski et al 2022;Khalil et al 2023). An appropriate mobile phase was finalized by optimizing different composition of mobile phase including ammonium acetate, acetic acid, aqueous ammonia at various strengths.…”
Section: Vaka Et Alsupporting
confidence: 59%
“…Even though its structure does not show chromophoric characteristics, it is reported that fosfomycin can be detected in the lowest UV range (below 190-200 nm). 18 However, it is a strenuous task to conduct analysis with commonly used solvents and buffers in this UV range. Also, inadequate retention in the reverse phase column due to the presence of a highly acidic, ionizable epoxide ring is observed.…”
Section: Introductionmentioning
confidence: 99%